Studi Tahap Perkembangan Mikrospora dan Respon Pepaya Hermaprodit Varietas Callina melalui Kultur Antera - Halimah Widyaningrum; Darda Efendi; Diny Dinarti; Megayani Sri Rahayu (Jurnal Hortikultura Indonesia, 2025)
Anther culture is an in vitro culture technique that is promising in obtaining haploid plants in one generation. This study aimed to obtain information regarding the stages of microspore development and anther response in three sizes of Callina papaya hermaphroditic flower buds on a callus induction medium. The research was conducted at the Microtechnics and Tissue Culture Laboratory 3, IPB- Bogor, from July to November 2022. The planting material used was three sizes of hermaphrodite flowers of the papaya variety Callina including small (10-15 mm), medium (16-20 mm) and large (21-25 mm). The culture medium used was MS medium with six PGR treatments, namely four combination treatments of (0.005, 0.01, 0.1 and 0.5 mg L-1) CPPU and (0.1 mg L-1) NAA; 0.1 mg L-1 BAP and 0.1 mg L-1 NAA; and 1.0 mg L-1 BAP and 2.0 mg L-1 NAA. The experimental design used a Randomized Complete Group Design (RCBD) with one factor (microspore development stage) and 2 factors (callus induction). The results showed that flowers measuring 10-15 mm had the highest percentage of uninucleate microspores (77.95%), a responsive size for inducing callus formation from anthers. Treatments of 0.5 mg L-1 CPPU and 0.1 mg L-1 NAA showed the highest percentage of anthers forming callus (40.4%). At the same time, flower size did not significantly influence the parameters observed, but 10-15 mm flower sizes showed the highest percentage of anthers forming callus (13%).Keywords: BAP, CPPU, callus induction, flower bud, NAA